Electric field-induced large strain and photoluminescence properties in SrRECoO4 (RE = Pr, Eu, Sm)-modified BNT-based ferroelectric ceramics. Issue 5 (1st March 2023) - Liu, Yang; Liu, Lulu; Li, Peng; Fu, Peng; Du, Juan; Li, Ziliang; Li, Huaiyong; Hao, Jigong; Li, Wei; Zeng, Huarong
Abstract: (1- x ) (0.935BNT–0.065BaTiO3 )- x SrRECoO4 (BNBT6.5- x SREC, RE = Pr, Eu, Sm)–based lead-free ferroelectric ceramics with large electrostrain and photoluminescence effect were prepared in our work. Through introducing the SREC dopant into BNBT6.5, the long-range ferroelectric order of ceramics was disrupted, inducing a weak polar state dominated by polar nanoregions before applying an electric field. Due to the reversible transition of PNRs under the electric field, the electrostrain was greatly promoted. When the content of SREC was 0.012, large field-induced large strains of 0.38–0.44% were obtained under an electric field of 70 kV/cm, equivalent to a large signal d 33 * ( S max / E max ) of 543–586 pm/V. Moreover, relying on the luminescence effect of RE 3+ ions in SREC, the modified ceramics exhibited strong photoluminescence with bright red or orange emissions, depending on the type of RE elements. However, the strong emission was strongly quenched in samples with a higher SREC content due to the photoluminescence quenching effect of the heavy metal (Co 3+ ) ions in the SREC dopant. The quenching model can be based on the formation of non-radiative recombination centers induced by Co 3+ ions, which affect the energy transition of RE 3+ ions from the excited state to the ground state.